Hard Times and Humanities Education. Who Reads Dickens Anymore? - MATEK, Ljubica (Anafora, 2023)
By focusing on the issue of education, the paper looks at Charles Dickens’s novel Hard Times (1854) which depicts a rationalist, positivist, and empirical focus of Thomas Gradgrind’s school. The education there is based on pure facts and forbids any form of imagination, artistic work and thinking, and particularly reading fiction. The events in the students’ lives serve as a means to question the validity and efficiency of such a utilitarian education, whereas the humanist education that Sissy Jupe has received from her family stands as an alternative to the strictly rationalist educational process. The conclusion emphasizes the necessity of educating the whole person as a socially and morally more acceptable option than merely educating people to become the work force. The role of literature and reading is foregrounded as crucial in the process of mat- uration, socialization, development of empathy and self-actualization.